1999
DOI: 10.1515/mgmc.1999.22.5.275
|View full text |Cite
|
Sign up to set email alerts
|

COMPLEXES OF BISMUTH(III) WITH AMINOPOLYCARBOXYLIC ACIDS. CRYSTAL STRUCTURES OF GUANIDINIUM AQUA(ETHYLENEDIAMINETETRAACETATO)BISMUTHATE(lll) AND AMINOGUANIDINIUM ETHYLENEDIAMINETETRAACETATOBISMUTHATE(III)

Abstract: In the crystal structure of guaninidium aqua(ethylenedi9minetetraacetato)bismuthate(III), the ethylenediaminetetraacetato tetraanion chelates to the bismuth atom through its two amino and four carboxyl oxygen atoms. A carboxylate bridge [Bi-0 = 2.694(4) A] links adjacent water-coordinated [Bi-O water = 2.673(4) A] ethylenediaminetetraacetatobismuthate(III) anions into a helical linear chain. The bismuth atom is eight-coordinate in a square-antiprismatic environment. The bismuth atom shows dodecahedral coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…For the reasons mentioned earlier, our interest is focused on precursor compounds which do not contain heteroelements or other metals in addition to the main one. The following Bi(III), La(III) and Pr(III) PAC complexes described previously in the literature and based on the various ligands used in this work fulfill this requirement: (13) and its aminoguanidinium (14) and b-alaninium (15) analogs, Bi(H 2 dtpa) Á O (20). This paper reports the preparation and characterization by FTIR and TGA of new complexes of Bi(III), La(III) and Pr(III) with edta, dtpa, ttha and egta ligands.…”
Section: Introductionmentioning
confidence: 94%
“…For the reasons mentioned earlier, our interest is focused on precursor compounds which do not contain heteroelements or other metals in addition to the main one. The following Bi(III), La(III) and Pr(III) PAC complexes described previously in the literature and based on the various ligands used in this work fulfill this requirement: (13) and its aminoguanidinium (14) and b-alaninium (15) analogs, Bi(H 2 dtpa) Á O (20). This paper reports the preparation and characterization by FTIR and TGA of new complexes of Bi(III), La(III) and Pr(III) with edta, dtpa, ttha and egta ligands.…”
Section: Introductionmentioning
confidence: 94%
“…When studying crystal structures of Pb(II) complexonates with anions of nitrilotriacetic ( H 3 Nta ) [2] and ethylenediaminetetraacetic ( H 4 Edta ) [3] acids, it was found that in Na[Pb(Nta)] [2], LEP is fully delocalized, while in Na 2 [ Pb ( Edta )] · 2 H 2 O [3], it is stereochemically active.…”
mentioning
confidence: 99%
“…In crystals of MPb(Nta) (where M is Na (V), K(VI), Cs (VII), NH 4 (VIII)) [2,3], the Pb and N atoms lie on a threefold axis. Each Pb atom in structures V-VIII is bonded in a tetradentate-chelate mode with three O atoms of another three ligands.…”
mentioning
confidence: 99%
See 2 more Smart Citations